La lectura: ¿un hábito que se construye en Ecuador? - López Mendoza, María Cecilia (2018)
The purpose of this research is based on showing the small advances that Ecuador has made in regards to reading habits, but in turn, how much it lacks. It analyzes the results that Ecuador has been experiencing in reading habits, such as the creation of its new National Reading Plan and the campaigns carried out. The research includes testimonies, figures and statements from different perspectives, such as: public government institutions, private institutions, reading enthusiasts, environmental experts and natural persons.